Word of Mouth Mediates the Effect of Marketing Mix on Students’ Decision to Choose Sabilal Muhtadin Islamic High School Banjarmasin - Muhammad Ridhonie; Muhammad Maladi; Ibrahim Daud; M. Isra Anwar; Surya Firdaus (Journal of International Conference Proceedings, 2022)
This study aims to analyze the effect of the marketing mix consisting of product, price, place, promotion on word of mouth. This study is also to examine the direct and indirect effects of the marketing mix consisting of product, price, place, promotion on student decisions, and finally the effect of word of mouth on student decisions. The population of this research is the students of SMA Islam Sabilal Muhtadin Banjarmasin. Samples were taken as many as 82 students who were selected as a whole through non-probability sampling. The data collected was analyzed by PLS-SEM (Partial Least Square-Structural Equation Modeling) analysis through the SmartPLS version 3.0 program. The results showed that only place has an effect on word of mouth while the influence of marketing mix on students' decisions to choose Sabilan Muhtadin Islamic High School was only for promotion and place. The latter is word of mouth does not mediate the influence of the marketing mix on students' decisions to choose this Islamic school. It is recommended much more effort is needed to create word of mouth and later will influence student’s decision or recommend others to choose the school. The place and promotion should be maintained in order to make more people join this Islamic High School. Keywords: Marketing mix, product, price, place and promotion, WoM and Students’ decision.